A wind farm control strategy for power reserve maximization. (February 2019) - Siniscalchi-Minna, Sara; Bianchi, Fernando D.; De-Prada-Gil, Mikel; Ocampo-Martinez, Carlos
Abstract: Nowadays, in many countries wind energy is responsible for a significant part of the electricity generation. For this reason, Transmission System Operators (TSOs) are now demanding the wind power plants (WPPs) to contribute with ancillary services such as frequency support. To this end, WPPs must be able to temporally increase the active power delivered into the grid to compensate consume and demand imbalances. This implies that WPPs now work below their maximum capacity to keep some power reserve to be able to inject extra power into the grid when needed. This reserve depends on the available wind power, which is directly connected with the wind speed faced by each turbine within the WPP. However, wind speed is negative affected by the wakes caused by the upstream turbines. This paper proposes a control algorithm to distribute the power contribution of each turbine seeking to minimize the wake effects and thus maximize the power reserve. The proposed algorithm is evaluated by simulations for the case of a WPP of 12 wind turbines. Highlights: A redistribution of the power contributions from each turbine improves power reserve. Generating larger power from the most downstream turbines improves available power. Frequency support is improved while the power demanded by the TSO is satisfied. Significant increase in power reserve is achieved compared to conventional strategies. Promising results are shown especially for low wind and high power demand conditions.